Chromatic changes in paintings of Adriano de Sousa Lopes after the removal of aged varnish - Linhares, João (2020)
The ability to digitally remove the varnish layer during the pre-conservation diagnostic of a painting, without any chemical or physical intervention, could be an advantage because it enables the prediction of the outcome of the cleaning procedure of the protective layer and contributes to the treatment proposal. Two paintings from Adriano de Sousa Lopes were investigated by hyperspectral imaging in the visible range, before and after the varnish layer removal. The spectral reflectance was estimated in each case and its comparison used to assess the effect of the varnish layer removal. The simulated paintings with the old varnish layer were compared with those restored, with no varnish, by comparing the chromaticity coordinates and other chromatic descriptors. It was found that considering the effect of the varnish layer of each painting individually produces lower errors than considering the average of the varnish layer across paintings. It was also found that simulating the varnish layer removal without knowing the varnish transmittance produces limited results and that the errors are smaller if the chromatic content is assessed without considering lightness.   Received: 2018-12-8 Revised: 2019-4-8 Accepted: 2019-4-29 Online: 2020-7-31 Publication: 2020-7-31